Mobile phone ownership and use of short text message service by farmer trainers: a case study of Olkalou and Kaptumo in Kenya - Kirui, Josephine; Kiptot, Evelyne; Maritim, Wesley; Wafula, Sylvia; Ngaina, Joshua; Kugonza, Jane (World Agroforestry Centre, 2015)
This paper presents the findings of a Rapid Appraisal (RA) study that was undertaken with 28 farmer trainers (FTs) to assess the use of the Short Message Service (SMS) in accessing agricultural information. The study was conducted in Kaptumo and Olkalou in Kenya. The study used RA tools that included discussions with key informants and semi-structured interviews guided by a checklist. The data and subsequent analysis revealed that all FTs owned mobile phones and were able to read and write text messages. English was the popular language among FTs in SMS usage (90% preference over other languages). The results further showed that information contained in text messages could be made useful immediately as all FTs read SMS received before the day ended. Additionally, the study indicated that FTs received agricultural text messages from fellow FTs (100% in Olkalou and71.4% in Kaptumo), service providers (50% in Kaptumo), extension workers (71.4% in Kaptumo), and local administration (78.6% in Kaptumo). The study further revealed that FTs occasionally share the text message information that they receive with other farmers. These findings point to the fact that the use of mobile phone technology is widely used by farmers to access and share agricultural information. Policy makers and extension service providers need to embrace this service so that farmers can access agricultural information in a timely and cost-effective manner.